EFEKTIVITAS UNCITRAL MODEL LAW ON ELECTRONIC TRANSFERABLE RECORDS (MLETR) 2017 DALAM MENDUKUNG DIGITALISASI PERDAGANGAN INTERNASIONAL STUDI KOMPARATIF IMPLEMENTASI DI AUSTRALIA DAN REPUBLIK RAKYAT TIONGKOK SERTA IMPLIKASINYA BAGI INDONESIA - Ahmad Nurafendi; Annie Myranika; Agus Eko Setyawan; Eduardo Retno; Ronald Pasrah (Berajah Journal, 2026)
The digitisation of international trade documents is a strategic imperative in the era of the global digital economy. The United Nations Commission on International Trade Law (UNCITRAL) has responded to this challenge through the 2017 Model Law on Electronic Transferable Records (MLETR), which provides a legal framework for the recognition of transferable electronic documents. This study analyses the effectiveness of the MLETR in supporting the digitisation of international trade through a comparative study of its implementation in Australia and the People’s Republic of China (PRC), whilst also evaluating its implications for Indonesia. Using a normative legal research method and a comparative approach, this study finds that Australia adopted the MLETR through comprehensive federal-state harmonisation, whilst the PRC integrated the principles of the MLETR into the revision of the Maritime Law 1992. Both approaches demonstrate that the success of MLETR implementation depends on inter-jurisdictional coordination, technological infrastructure, and industry awareness. For Indonesia, which only ratified the United Nations Convention on the Use of Electronic Communications in International Contracts 2005 in 2023, the implementation of the MLETR is a prerequisite for competitiveness in global digital trade. This study recommends the adoption of the MLETR through amendments to the ITE Law and the Trade Law, as well as the establishment of a National Electronic Trade Council to coordinate implementation.